2016
DOI: 10.1016/j.ijporl.2016.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Deaf or hard of hearing children in Saudi Arabia: Status of early intervention services

Abstract: Abstract:Objective: To determine the status of early intervention services provided to children who are deaf or hard of hearing and their parents/caregivers from birth to five years of age at two main state hospitals in Riyadh, Saudi Arabia, based on their parents' perceptions. Method: A descriptive quantitative research design was used to determine the status of early intervention services for deaf or hard of hearing children in Saudi Arabia based on their parents' perceptions. Semistructured interviews based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Parents play an important role in the literacy development of their children. In the case of children who are hearing impaired, studies have revealed delays in literacy for those born to hearing parents because of the associated delays in the children's exposure to SL (Alyami, Soer, Swanepoel, & Pottas, 2016;Geeslin, 2008). Due to the significance of parental influence, there was a questionnaire designed to identify patterns relating to the literacy of the children who were hearing impaired from the parents' perspective.…”
Section: User Studymentioning
confidence: 99%
“…Parents play an important role in the literacy development of their children. In the case of children who are hearing impaired, studies have revealed delays in literacy for those born to hearing parents because of the associated delays in the children's exposure to SL (Alyami, Soer, Swanepoel, & Pottas, 2016;Geeslin, 2008). Due to the significance of parental influence, there was a questionnaire designed to identify patterns relating to the literacy of the children who were hearing impaired from the parents' perspective.…”
Section: User Studymentioning
confidence: 99%
“…The available studies on this topic focused mainly on how parents value the access to diagnosis and early intervention [9,10], to early literacy [11], or to the mainstream schools through the adequate provision of educational services [12]. From these studies, it can be highlighted that DHH children and their families are still facing important obstacles to access the necessary services, such as: important delays in the first diagnosis and treatment of hearing loss [9]; poor communication of hearing screening results, inconsistencies in healthcare information from primary care providers, and lack of local resources [10]; an inadequate access to literacy during preschool activities [11]; or a lack of collaboration with special educator in mainstream schools [12].…”
Section: The Access To Services and Supports Of Deaf And Hard-of-hearmentioning
confidence: 99%
“…In many cases, although services were available, they remained elusive for parents who lived in remote areas. As research has shown [9,10], living in a rural or remote geographical locations limits the access to social and health services and put families at risk. There are models of hearing-health care for children who live with their families in remote areas where services are found to be cost effective.…”
Section: Bringing and Adapting The Services To The Rural Settingsmentioning
confidence: 99%
“…According to the General Authority for Statistics in Saudi Arabia (SA), 1.4% of all citizens have mild, moderate or severe hearing difficulties [ 6 ]. The prevalence of hearing loss in SA may vary according to the region where the prevalence of hearing loss increases in rural areas [ 7 ]. Previous Saudi studies showed different prevalences of hearing loss ranging from 1.75% to 7.12% [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%